Developing Educational Game Application for Chemistry Periodic Table - Wijaya, Antonius Gunawan; Nugroho, Erdhi Widyarto; Harnadi, Bernardinus (SISFORMA, 2024)
Chemistry is one of the elective subjects and cross-interest subjects taught at the high school level or equivalent secondary education. The periodic table is a chart that contains the names and types of chemical elements grouped according to their similarities and properties. In current learning, more than 75% of high school students still face difficulties in naming elements in the periodic table, especially in understanding the periodic system and the regularities of the chemical properties of these elements. Conventional teaching methods often bore students, and there is a need for engaging learning media to enhance the learning outcomes. With the increasing use of Android gadgets, where students use Android devices for classes, learning through games on Android can be effective. This game is designed using Unity in 2D format and is built for the Android platform, specifically for chemistry education in grade X of high school. The chosen game design method for this application is the waterfall method. The result of this research is the game "Chem Ball" for educating Group A periodic table elements for high school grade X students. The game was tested with five high school students, and the results indicate that students are assisted in learning the periodic table of chemistry (memorizing, understanding, and recalling the sequence of elements in the periodic table) through the attractive and interactive interface of the "Chem Ball" game. "Chem Ball" is also proven to be easy and practical for high school students to play. After playing the game, students feel that learning the periodic table of chemistry has become easier.